ASPEK SOSIAL EKONOMI DAN KAITANNYA DENGAN MASALAH GIZI KURANG DI KABUPATEN MANGGARAI, NUSA TENGGARA TIMUR - Ursula Dianita Marut (Food and Nutrition Society of Indonesia, 2007)
The objective of this study is to analyze the relationship between socio-economic and cultural aspects and undernutrition problem in Kabupaten Manggarai, Nusa Tenggara Timur. This research was designed as cross sectional study with purposive method. This research was conducted in Desa Meler, Kecamatan Ruteng, Kabupaten Manggarai from June to July 2007. Primary data and secondary data were collected in this study. Primary data including family’s socio-economic characteristics, nutritional status, environment sanitation and food consumption using interview questionnaire. Secondary data including food production, prevalence of nutritional status of the children under five, and were collected from some Government’s institutions. Populations of this research were children under five in Desa Meler. Samples consisted of 80 children and were classified into two groups, a total of 48 classified as undernutrition group and the rest of them belong to normal group. Result shows that the prevalence of undernutrition of children under five in Manggarai year 2005 is 22,75 % and have decreased in 2006 become 19,24 %. Poverty is one of the causal factors of this undernutrition problem in Manggarai.